2009
DOI: 10.1063/1.3076320
|View full text |Cite
|
Sign up to set email alerts
|

Slow photoelectron velocity-map imaging spectroscopy of C2N−, C4N−, and C6N−

Abstract: High resolution photoelectron spectra of C(2)N(-), C(4)N(-), and C(6)N(-) anions are reported, obtained using slow electron velocity-map imaging. The spectra show well resolved transitions to the X (2)Pi neutral ground state of all three species and to the a (4)Sigma(-) excited state of C(2)N and C(4)N. This study yields the adiabatic electron affinity of C(2)N, C(4)N, and C(6)N, the spin-orbit splitting in the X (2)Pi state of each radical, and the term energy of the a (4)Sigma(-) state in C(2)N and C(4)N. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 49 publications
13
50
0
Order By: Relevance
“…As this radical is isoelectronic with CCN, a similar excited state may also be important to the spectroscopy of the present investigation, especially in terms of its interaction via spin-orbit coupling. The MRCI calculations (including zero point correction) of Pd and Chandra 3 predicted the a 4 Σ -state to be 8322 cm -1 higher than the ground state for CCN, which is in good agreement with the recent observation of this state by slow photoelectron velocity-map imaging spectroscopy by Neumark and co-workers, 22 T 0 = 8413 ± 8 cm -1 .…”
Section: Introductionsupporting
confidence: 87%
“…As this radical is isoelectronic with CCN, a similar excited state may also be important to the spectroscopy of the present investigation, especially in terms of its interaction via spin-orbit coupling. The MRCI calculations (including zero point correction) of Pd and Chandra 3 predicted the a 4 Σ -state to be 8322 cm -1 higher than the ground state for CCN, which is in good agreement with the recent observation of this state by slow photoelectron velocity-map imaging spectroscopy by Neumark and co-workers, 22 T 0 = 8413 ± 8 cm -1 .…”
Section: Introductionsupporting
confidence: 87%
“…The latter results are supported by the SEVI experiments of Garand et al and Yen et al [21,22]. Botschwina et al performed a detailed theoretical analysis of the C 2n+1 N − ( = 1-6) anions using coupled cluster theory combined with large basis sets and predicted, among other spectroscopic constants, their equilibrium structures as well as harmonic ( = 1-6) and anharmonic ( = 1-3) vibrational frequencies [18,24].…”
Section: Introductionmentioning
confidence: 79%
“…In their matrix studies, which mainly focused on the electronic transitions of C 2n+1 N − ( = 2-6) anions, Grutter et al [19] also reported the IR absorption spectra of the smaller anions and found evidence for a few IR transitions for C 5 N − , C 7 N − and C 9 N − . Garand et al and Yen et al [21,22] investigated the anion photoelectron spectra of the C n N − ( = 2-6) clusters using slow electron velocity-map imaging (SEVI) and determined adiabatic electron affinities for C 3 N and C 5 N, as well as vibrational frequencies for the fundamentals of the degenerate cis (538 cm −1 ) and trans (208 cm states for the anions with odd and even number of carbon atoms, respectively [23].…”
Section: Introductionmentioning
confidence: 99%
“…The gas mixture, at a stagnation pressure of 300 psi, was expanded into the source vacuum chamber through an EvenLavie pulsed valve 49 equipped with a grid discharge described in detail in Ref. 50. Anions formed in the gas expansion were perpendicularly extracted into a Wiley-McLaren TOF-MS (Ref.…”
Section: Slow Electron Velocity-map Imagingmentioning
confidence: 99%